Meaning In The Last Unicorn Novel By Peter Beagle - Syauta, Greselda E.; Moelier, Dahlia D.; Abeng, Andi Tenri (Humaniora: Journal of Linguistics, Literature, and Education, 2025)
This study explores the use of figurative language in Peter Beagle's The Last Unicorn, analyzing how it enhances narrative depth and reader engagement. The research aims to deepen understanding of how figurative language enriches literary analysis and emotional resonance. This research employs a descriptive qualitative approach by Moleong to comprehensively analyze figurative language in Peter Beagle’s The Last Unicorn (1968). Using Tarigan’s (1986) classification and Parera’s (2004) contextual meaning theory, the study systematically identifies, categorizes, and analyzes figurative expressions, providing in-depth insights into the novel’s symbolic depth. This study examines the use of figurative language in Peter Beagle’s The Last Unicorn, applying Tarigan's theory to identify simile, metaphor, personification, hyperbole, synecdoche, and euphemism. These literary devices enrich Beagle’s magical world, deepening emotional engagement and thematic complexity, transforming the novel into a poetic narrative that resonates through its blend of fantasy and realism. This study reveals how figurative language, particularly metaphors, plays a crucial role by enriching descriptions, deepening themes, and enhancing emotional resonance, these devices transform the novel's storytelling. Metaphors, in particular, provide insight into characters and their journeys, making the narrative more relatable and engaging for readers on a profound level.